REVOLUTIONIZING HEALTHCARE EDUCATION: THE INTEGRATION OF AI IN CLINICAL TRAINING PROGRAMS - Anil Kumar Reddy Avula (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
Integrating artificial intelligence in healthcare education represents a transformative shift in how medical professionals are trained and evaluated. This comprehensive article examines AI technologies' implementation, impact, and challenges across various aspects of healthcare education, including clinical simulations, performance analytics, virtual patient interactions, and decision support systems. The article explores how AI-enhanced training environments have revolutionized traditional apprenticeship models, leading to improved clinical competencies, reduced training times, and optimized resource utilization. Through a detailed examination of multiple healthcare institutions and educational programs, this research demonstrates the significant advantages of AI integration in medical training while addressing the technical challenges and solutions in implementing these advanced systems.